2020
DOI: 10.21203/rs.2.16188/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nasogastric tube feeding versus assisted hand feeding in-home healthcare older adults with severe dementia in Taiwan: a prognosis comparison

Abstract: Backgrounds: All individuals with severe dementia should be offered careful hand feeding. However, under certain circumstances, people with severe dementia have a feeding tube placed. In Taiwan, tube feeding rate in demented older home care residents is increasing however, the benefits of tube feeding in this population remain unknown. We compared the clinical prognosis and mortality of older patients with severe dementia receiving nasogastric tube feeding (NGF) or assisted hand feeding (AHF).Methods: This ret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…8 This study found that CHF was associated with lower pneumonia risk among patients who survived to discharge. In contrast, Chou et al 17 found no difference in pneumonia risk between NGF and assisted hand feeding patients receiving home-based health care in Taiwan. These varying results can Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…8 This study found that CHF was associated with lower pneumonia risk among patients who survived to discharge. In contrast, Chou et al 17 found no difference in pneumonia risk between NGF and assisted hand feeding patients receiving home-based health care in Taiwan. These varying results can Fig.…”
Section: Discussionmentioning
confidence: 91%
“…8,15 Two studies that focused on NGF showed mixed results on mortality risk. 16,17 Additional studies on NGF are needed given this is the predominant type of enteral feeding used in people with dementia in many Asian countries including China, Taiwan, and Singapore. 18e20 In Hong Kong, a study reported that the prevalence of NGF was 53% among residents with advanced cognitive impairment in 66 residential care homes.…”
mentioning
confidence: 99%